The White Cane: An Ethnographic Account on the Widespread Ambivalence Amongst Visually Impaired Towards an Iconic Aid - Maria Bäckman (Scandinavian Journal of Disability Research, 2024)
Many people with acquired or progressive visual impairments often exhibit reluctance towards using the white cane. This article employs a qualitative ethnographic approach to gain a deeper understanding of why some individuals might opt not to utilize the white cane, a tool widely acknowledged for its assistance in enhancing mobility and promoting independence. Based on fieldwork conducted at a Low Vison and Resource Centre in Sweden, which involved interviews with both new and experienced white cane users, as well as low vision teachers and therapists at the center, the study is aiming at more profound knowledge of the exposed position in society of visually impaired people. Additionally, it is argued that by recognizing the cane as a physical object within the human environment, we can gain further insight into the conflicting emotions experienced by individuals with acquired or progressive visual impairments. The article’s overall conclusion suggests that the resistance towards this iconic aid is quite reasonable. The white cane inevitably prevents any attempt to pass as a fully sighted person, as it identifies the user as someone who differs from normative and ableist expectations regarding bodily function.